(x-8/4)+(x+5/5)=6+(x+2/11)

Simple and best practice solution for (x-8/4)+(x+5/5)=6+(x+2/11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-8/4)+(x+5/5)=6+(x+2/11) equation:



(x-8/4)+(x+5/5)=6+(x+2/11)
We move all terms to the left:
(x-8/4)+(x+5/5)-(6+(x+2/11))=0
We add all the numbers together, and all the variables
(x-2)+(x+1)-(6+(+x+2/11))=0
We get rid of parentheses
x+x-(6+(+x+2/11))-2+1=0
We multiply all the terms by the denominator
x*11))+x*11))-(6+(+x+2-2*11))+1*11))=0
We add all the numbers together, and all the variables
x*11))+x*11))-(6+(x-20))+1*11))=0
Wy multiply elements
1331x^4=0
We do not support expression: x^4

See similar equations:

| X/x-3=6/10 | | -9v+21=-4(v-9) | | 5(-3)+2y=-7 | | 8+x+3x=180 | | 30000((0.65x-32500)-300000)=15000(0.65x-107250) | | 8x^2-65x-63=(5x+3) | | 2((0.65x-32500)-300000)=(0.65x-107250) | | 3x-2.6=x+9.2 | | 4=y/8+1 | | 2x+17=16-4 | | 4x-3=x+10 | | −6/t−7=17 | | 4b+5=13 | | (5x-66)-30=(5x-66) | | -3(3)+y=15 | | X^2+x+7=19 | | 6x=2x^2/3 | | -8p+3=-125 | | 2x5=17 | | 36=((2x+2)(3x))/2 | | x-5(-4)=20 | | u/2+11=26 | | 72=6x(x+1) | | (x2+6x+9)3/4-13=14 | | -3(x+5)-2=-32 | | |2x|=4 | | 6x2+-14x+4=0 | | 4x-1=9x-22 | | 3(x-3)-12=-9 | | 68+y=96+X | | 3+9p^2=4 | | (6x+6x)+3(2+3)=39 |

Equations solver categories